The Impact of the EU Regional Policy in Romania - Iuliana-Noemi Bomher (CES Working Papers, 2011)
Europeanization is a valuable concept for explaining the impact of EU policies at domestic level and especially of regional policy development in Romania. The relative low discrepancies and the low levels of development that Romania faced after almost fifty years of centralized planning resulted apparently in no need for a regional policy. This policy was `built' in order to meet the EU financial assistance and Romania had to re-think its centre-region relation and to acquire a new vision over the policy of regional development. The following paper will try to analyze whether the current regional policy managed to have the expected impact in Romania, with short emphasis on the concepts of regionalism, regional competitiveness and economic agglomerations.
Keywords: 330; regional policy; identity; competitiveness; agglomerations Romania